2020
DOI: 10.3390/app10124325
|View full text |Cite
|
Sign up to set email alerts
|

An Ordinary State-Based Peridynamic Model for Fatigue Cracking of Ferrite and Pearlite Wheel Material

Abstract: To deal with a new-developed ferrite and pearlite wheel material named D1, an alternative ordinary state-based peridynamic model for fatigue cracking is introduced due to cyclic loading. The proposed damage model communicates across the microcrack initiation to the macrocrack growth and does not require additional criteria. Model parameters are verified from experimental data. Each bond in the deformed material configuration is built as a fatigue specimen subjected to variable amplitude loading. Fatigue crack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Accordingly, literature concerning peridynamic theory is quite exhaustive and abundant. In the past two decades, several peridynamic studies pertaining to elastic deformation and fracture solids [2,[26][27][28], brittle fracture [29][30][31][32][33], fatigue failure [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], and PD application of damage in composites [33,43,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] have been reported. Studies related to crack initiation and propagation using peridynamics can be found in [30,[66][67][68][69].…”
Section: Review Of Peridynamic Theorymentioning
confidence: 99%
“…Accordingly, literature concerning peridynamic theory is quite exhaustive and abundant. In the past two decades, several peridynamic studies pertaining to elastic deformation and fracture solids [2,[26][27][28], brittle fracture [29][30][31][32][33], fatigue failure [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], and PD application of damage in composites [33,43,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] have been reported. Studies related to crack initiation and propagation using peridynamics can be found in [30,[66][67][68][69].…”
Section: Review Of Peridynamic Theorymentioning
confidence: 99%
“…The test data show that the reduction in stiffness and strength is good agreement with the peridynamic simulation results. The results indicate that the ordinary peridynamic fatigue damage model can deal with the details of crack initiation and growth without extra rules [58][59][60].…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, PD can predict damage development without additional assumptions as in the CCM, for example, crack extension criteria and node enrichment functions. PD provides a powerful tool to analyze material and structural failure processes [4,5], and has already been successfully applied to various problems, such as deformation and fracture simulation for brittle materials [6][7][8][9][10][11], asphalt [12], ferrite and pearlite wheel materials [13] and composite beams [14], etc.…”
Section: Introductionmentioning
confidence: 99%